\(-1x^4+3x^2-5x^3-3-x\)

P(x)= 

K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

15 tháng 5 2019

a)

\(Q\left(x\right)=-1x^4+3x^2-5x^3-3-x\)

Sắp xếp: \(Q\left(x\right)=-1x^4-5x^3+3x^2-x-3\)

\(P\left(x\right)=5x^3+2x^2+1x^4+4+x\)

Sắp xếp: \(P\left(x\right)=1x^4+5x^3+2x^2+x+4\)

b)

\(Q\left(x\right)+P\left(x\right)=\left(-1x^4+3x^2-5x^3-x-3\right)+\left(1x^4+5x^3+2x^2+x+4\right)\)

\(=-1x^4-3x^2-5x^3-x-3+1x^4+5x^3+2x^2+x+4\)

\(=\left(-1x^4+1x^4\right)+\left(-3x^2+2x^2\right)+\left(-5x^3+5x^3\right)+\left(-x+x\right)+\left(-3+4\right)\)

\(=-1x^2+1\)

Vậy P(x) + Q(x) = -1x2 + 1

\(Q\left(x\right)+P\left(x\right)=\left(-1x^4+3x^2-5x^3-x-3\right)-\left(1x^4+5x^3+2x^2-x-4\right)\)

\(=-1x^4+3x^2-5x^3-x-3-1x^4-5x^3-2x^2-x-4\)

\(=\left(-1x^4-1x^4\right)+\left(3x^2-2x^2\right)+\left(-5x^3-5x^3\right)+\left(x-x\right)+\left(-3-4\right)\)

\(=-2x^4+x^2-10x^3-7\)

Vậy P(x) - Q(x) = -2x4 + x2 - 10x3 - 7

20 tháng 9 2019

a)

Q\left(x\right)=-1x^4+3x^2-5x^3-3-xQ(x)=−1x4+3x2−5x3−3−x

Sắp xếp: Q\left(x\right)=-1x^4-5x^3+3x^2-x-3Q(x)=−1x4−5x3+3x2−x−3

P\left(x\right)=5x^3+2x^2+1x^4+4+xP(x)=5x3+2x2+1x4+4+x

Sắp xếp: P\left(x\right)=1x^4+5x^3+2x^2+x+4P(x)=1x4+5x3+2x2+x+4

b)

Q\left(x\right)+P\left(x\right)=\left(-1x^4+3x^2-5x^3-x-3\right)+\left(1x^4+5x^3+2x^2+x+4\right)Q(x)+P(x)=(−1x4+3x2−5x3−x−3)+(1x4+5x3+2x2+x+4)

=-1x^4-3x^2-5x^3-x-3+1x^4+5x^3+2x^2+x+4=−1x4−3x2−5x3−x−3+1x4+5x3+2x2+x+4

=\left(-1x^4+1x^4\right)+\left(-3x^2+2x^2\right)+\left(-5x^3+5x^3\right)+\left(-x+x\right)+\left(-3+4\right)=(−1x4+1x4)+(−3x2+2x2)+(−5x3+5x3)+(−x+x)+(−3+4)

=-1x^2+1=−1x2+1

Vậy P(x) + Q(x) = -1x2 + 1

Q\left(x\right)+P\left(x\right)=\left(-1x^4+3x^2-5x^3-x-3\right)-\left(1x^4+5x^3+2x^2-x-4\right)Q(x)+P(x)=(−1x4+3x2−5x3−x−3)−(1x4+5x3+2x2−x−4)

=-1x^4+3x^2-5x^3-x-3-1x^4-5x^3-2x^2-x-4=−1x4+3x2−5x3−x−3−1x4−5x3−2x2−x−4

=\left(-1x^4-1x^4\right)+\left(3x^2-2x^2\right)+\left(-5x^3-5x^3\right)+\left(x-x\right)+\left(-3-4\right)=(−1x4−1x4)+(3x2−2x2)+(−5x3−5x3)+(xx)+(−3−4)

=-2x^4+x^2-10x^3-7=−2x4+x2−10x3−7

Vậy P(x) - Q(x) = -2x4 + x2 - 10x3 - 7

8 tháng 4 2018

k mk di

15 tháng 5 2017

a) x5-3x2+x4-\(\dfrac{1}{2}\)x-x5+5x4+x2-1

= (x5-x5)+(x4+5x4)+(x2-3x2)-\(\dfrac{1}{2}\)x-1

= 6x4-2x2-\(\dfrac{1}{2}\)x-1

b) x-x9+x2-5x3+x6-x+3x9+2x6-x3+7

= (3x9-x9)+(2x6+x6)-(5x3+x3)+x2+(x-x)+7

= 2x9+3x6-6x3+x2+7

4 tháng 4 2017

a) \(A=\)\(x^4\)\(+4x^3\)\(+2x^2\)\(+x\)\(-7\)

  \(B=\)\(2x^4\)\(-4x^3\)\(-2x^2\)\(-5x\)\(+3\)

b) f(x)= A(x)+B(x)= \(3x^4-4x\)\(-4\)

    g(x)=A(x)-B(x) =  \(-x^4+8x^3+4x^2+6x\)\(-10\)

c) g(x)= \(0^4+8.0^3+4.0^2\)\(+6.0\)\(-10\)

         = -10

   g(-2)=\(-2^4+8.-2^3+4.-2^2+6.-2\)\(-10\)

         =\(-54\)

20 tháng 4 2018

\(M\left(x\right)=P\left(x\right)+Q\left(x\right)=2,5x^6-4+2,5x^5-6x^3+2x^2\)-5x+\(3x-2,5x^6-x^2+5-2,5x^5+6x^3\)

=\(\left(2,5x^6-2,5x^6\right)\)+\(\left(2,5x^5-2,5x^5\right)\)\(\left(-6x^3+6x^3\right)\)+\(\left(2x^2-x^2\right)\)+\(\left(-5x+3x\right)\)+(-4+5)

= \(x^2-2x+1\)

9 tháng 1 2020

\(P\left(x\right)+Q\left(x\right)=f\left(x\right)-g\left(x\right)\)

\(f\left(x\right)-g\left(x\right)=3x^4+3x^3-5x^2+x-5-x^4-3x^3+3x^2-5x+7\)

\(=2x^4-2x^2-4x+2\)

\(\Rightarrow P\left(x\right)+Q\left(x\right)=2x^4-2x^2-4x+2\left(1\right)\)

\(P\left(x\right)-Q\left(x\right)=g\left(x\right)+h\left(x\right)\)

\(g\left(x\right)+h\left(x\right)=x^4+3x^3-3x^2+5x-7+5x^4+2x^3+x^2-5\)

\(=6x^4+5x^3-2x^2+5x-12\)

\(\Rightarrow P\left(x\right)-Q\left(x\right)=6x^4+5x^3-2x^2+5x-12\left(2\right)\)

Từ ( 1 );( 2 ) thì tìm dc P(x) và Q(x)